The Effect of Self-Efficacy and Happiness at Work on Employee Resignation Rates Through Servant Leadership (Study at PNM Mekaar PT. Permodalan Nasional Madani, Balikpapan Branch) - Lulut Endah Susanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to investigate, via employee servant leadership at PT. Permodalan Nasional Madani, Balikpapan Branch, the relationship between turnover intention and self-efficacy and job satisfaction. This study employs a quantitative methodology utilizing IBM Statistics SPSS 26.0 and the PLS tool for structural equation modeling (SEM). The workers at the Balikpapan Branch of PT. Permodalan Nasional Madani serve as the study's unit of analysis. The sample size is made up of 117 participants. A questionnaire that was sent online was used as the data gathering method. The study's findings demonstrate that self-efficacy and job satisfaction might moderate the impact of these factors on employees' intentions to leave PT. Permodalan Nasional Madani, Balikpapan Branch